2010
DOI: 10.1097/qai.0b013e3181cc4f4a
|View full text |Cite
|
Sign up to set email alerts
|

Acute Infection of Chinese Macaques by a CCR5-Tropic SHIV Carrying a Primary HIV-1 Subtype B' Envelope

Abstract: The increasing prevalence of HIV-1 subtype B' in China and Southeast Asia calls for efforts to develop a relevant animal model to study viral transmission and pathogenesis. Because there are significant differences between subtype B' HIV-1 and other chimeric simian/human immunodeficiency viru (SHIVs) in the env gene, a novel SHIV, designated SHIV(B'WHU), was generated by replacing counterparts of SHIV(SF33) with tat/rev/vpu/env genes derived from a primary, CCR5-tropic, subtype B' HIV-1 strain of a Chinese pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Flow cytometry was performed for the staining of T lymphocytes as we previously described (Chen et al 2000; Chen et al 2002; Wang et al 2010). Peripheral CD4 + T-cell counts were calculated by multiplying the percentage of CD3 + CD4 + T cells with the total CD3 + T lymphocytes using the BD Trucount™ method .…”
Section: Methodsmentioning
confidence: 99%
“…Flow cytometry was performed for the staining of T lymphocytes as we previously described (Chen et al 2000; Chen et al 2002; Wang et al 2010). Peripheral CD4 + T-cell counts were calculated by multiplying the percentage of CD3 + CD4 + T cells with the total CD3 + T lymphocytes using the BD Trucount™ method .…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al compared infection of Chinese RM with two different SIV strains, SIVmac251 and SIVmac239, and observed that SIVmac239 infection was more pathogenic, as it caused more aggressive disease than SIVmac251 [9], suggesting the potential variability of bio-clinical parameters in Chinese RM when infected by different strains of SIV. Wang et al [23] showed that a CCR5-tropic chimeric SHIV (SHIV B’WHU ) could replicate in Chinese RM peripheral blood and cause acute infection of these animals with no significant changes in viral tropism and sequences after infection. Miyake et al [24] infected Chinese RM with pathogenic SHIV (SHIV-C2/1-KS661c) by intrarectal inoculation and observed rapid dissemination of SIV to multiple organs, including rectum, thymus and axillary lymph node (LN) as early as three days post infection.…”
Section: Reviewmentioning
confidence: 99%
“…To investigate the specificity of TD-0680, we first adopted a single-cycle infectivity assay using GHOST(3)-CD4-X4R5 as target cells (4,26). HIV-1 NL4 -3 luciferase reporter viruses were pseudotyped with different Envs, including R5-tropic HIV-1 ADA , X4-tropic HIV-1 HxB2 , and multi-tropic VSV-G. Before exposure to pseudovirions, cells were pretreated with 1 M maraviroc, TD-0232, TD-0680, or JM2987 (a CXCR4 antagonist) (27).…”
Section: Anti-hiv-1 Specificity Of Ccr5mentioning
confidence: 99%